Сутність і призначення соціальної держави в контексті правового досвіду сучасної України: теоретико-правовий аналіз - Полесов, С. С.; Polesov, S. S. (Вісник Харківського національного університету внутрішніх справ. – 2024. – № 1 (104), ч. 1. - С. 31-43, 2024)
У статті доведено, що соціальна держава наділена низкою важливих правових ознак і характеристик, які можна виокремити на підставі системного аналізу конституційних норм. Концепт соціальної держави подано в Конституції України у гранично узагальненій формі, без конкретизації проявів соціальної держави, її ознак, функцій, завдань тощо. Показано, що наявна модель соціальної держави як константна і визначальна юридична характеристика держави Україна заразом не є сталою в конституційному сенсі, вона потребує свого розвитку і зміцнення.

The concept of the social state is one of the elements of the constitutional identity of Ukraine. In the context of the Constitution of Ukraine, the social state is endowed with a number of important legal features and characteristics that can be distinguished on the basis of a systematic analysis of constitutional norms, where the concept of the social state is directly mentioned. This concept is included among the fundamental legal characteristics of the Ukrainian state and, at the same time, among the defining characteristics of the Ukrainian constitutional system. It is presented in the Constitution of Ukraine in an extremely generalized form, without specifying the manifestations of the social state, its features, functions, tasks, etc. The characteristics of the Ukrainian state as a social state cannot be changed in any other way than by amending the Constitution of Ukraine in a particularly complicated constitutional procedure. Any changes in the constitutional and legislative organization of state power or in its implementation should not take place if they are inconsistent with the legal nature of Ukraine as a social state, or directly or indirectly contradict the essence and purpose of the social state as such. The characteristic of the Ukrainian state as a social one is used in the constitutional text as independent, separate, self-sufficient next to other similar, but not identical in the legal sense, characteristics of the same state, such as “democratic” and “legal”. At the same time, the concept of a social state cannot be identified with the concepts of a democratic or legal state, nor can it be defined through them, through their signs, features, and manifestations. The simultaneous application in relation to Ukraine of its constitutional definition as a social state and, next to it, as a democratic and legal state leads to the presence of complex relationships between these characteristics, where each of them acts as an independent manifestation of the current and prospective state existence of Ukraine, but at the same time, all these manifestations have a constitutional and legal character and reflect a certain section of the essence of this state. It should be emphasized that there is an essential connection between the existence of the social state and the functional purpose of the Constitution of Ukraine: the latter, as follows from its preamble, is aimed, in particular, at the development and strengthening of the social state in Ukraine. The concept of the development and strengthening of the social state indicates the constitutionally defined context of its dynamic existence: the existing model of the social state, being a constant and defining legal characteristic of the state of Ukraine, is nevertheless not stable in the constitutional sense, it needs its development and strengthening, first, in the interests of the Ukrainian people, secondly, in a direction that should not lead to distortion of the essence and purpose of the social state, distortion or emasculation of its essence and purpose, thirdly, such development and strengthening should take place within the framework defined by the Constitution of Ukraine.

В статье подтверждено, что социальное правительство наделено рядом принципиальных правовых признаков и черт, которые можно выделить на основании системного анализа конституционных норм. Концепт социального государства представлен в Конституции Украины в предельно обобщенной форме, без конкретизации проявлений социального государства, его признаков, функций, задач и т.д. Показано, что существующая модель социального государства как константная и определяющая юридическая характеристика государства Украина не является постоянной в конституционном смысле, она требует своего развития и укрепления.
The essence and purpose of the social state in the context of the legal experience of modern Ukraine: theoretical and legal analysis
Keywords: Конституція України; соціальна держава; демократична держава; правова держава; соціальні права громадян; соціальна політика; Конституційний Суд України; Ukraine; Constitution of Ukraine; social state; democratic state; rule of law; social rights of citizens; social policy; Constitutional Court of Ukraine; Конституция Украины; социальное государство; демократическое государство; правовое государство; социальные права граждан; социальная политика; Конституционный суд Украины